New development: Are the holding companies as a hybrid governance model reinforcing the control on municipal corporations?. Issue 1 (2nd January 2023) - Grossi, Giuseppe; Thomasson, Anna
IMPACT: The authors recommend that politicians and public managers consider the possible benefits and critical issues connected to the creation of holding companies at the local government level. On the one hand, municipal holding companies can be useful for steering and controlling municipal corporations; on the other hand, they can have the downside of adding another level of governance.